A Subpopulation of Schwann Cell-Like Cells With Nerve Regeneration Signatures Is Identified Through Single-Cell RNA Sequencing - Wei, Zairong; Shu, Shenyou; Zhang, Mingjun; Xie, Sitian; Tang, Shijie; Nie, Kaiyu; Li, Haihong (Frontiers in Physiology, 2021)
Schwann cell-like cells (SCLCs) derived from human amniotic mesenchymal stem cells (hAMSCs) have been shown to promote peripheral nerve regeneration, but the underlying molecular mechanism was still poorly understood. In order to investigate the heterogeneity and potential molecular mechanism of SCLCs in the treatment of peripheral nerve regeneration at a single cell level, single-cell RNA sequencing was applied to profile single cell populations of hAMSCs and SCLCs. We profiled 6,008 and 5,140 single cells from hAMSCs and SCLCs, respectively. Based on bioinformatics analysis, pathways associated with proliferation, ECM organization, and tissue repair were enriched within both populations. Cell cycle analysis indicated that single cells within these two populations remained mostly in the G0/G1 phase. The transformation of single cells from hAMSCs to SCLCs was characterized by pseudotime analysis. Furthermore, we identified a subpopulation of SCLCs that highly expressed genes associated with Schwann cell proliferation, migration, and survival, such as JUN, JUND, and NRG1. Genes such as PTGS2, PITX1, VEGFA, and FGF2 that promote nerve regeneration were also highly expressed in single cells within this subpopulation, and terms associated with inflammatory and tissue repair were enriched in this subpopulation by pathway enrichment analysis. Our results indicate that a subpopulation of SCLCs with nerve regeneration signatures may be the key populations that promote nerve regeneration.